A Systematic Review of Effective Techniques For Overcoming Difficulties in Academic Writing - Nurjadi, Nurjadi; Ilham, Ilham; Irwandi, Irwandi (English Education Department, 2025)
This study explores the challenges students face in academic writing and identifies effective techniques that can help overcome these problems. The research background shows that academic writing skills are essential for students and researchers, but many face difficulties in organising ideas, following writing guidelines, and structuring arguments logically. Using a qualitative approach, this study applied systematic literature review (SLR) to collect data from in-depth interviews and observations of students and researchers. The results showed that good planning, clear language use, and peer feedback significantly improved the quality of writing. In addition, techniques such as mind mapping and the use of writing aids were also shown to support a more systematic writing process. This study fills a gap in the literature by highlighting the lack of integration of various academic writing techniques and the influence of external factors such as social support and stress levels on the effectiveness of these techniques. The findings are expected to provide guidance for academic writers in selecting techniques appropriate to the challenges faced and provide insights for educators in supporting the development of students' writing skills.